Lineage and virulence of Streptococcus suis serotype 2 isolates from North America - Fittipaldi N. (2017)
We performed multilocus sequence typing of 64 North American Streptococcus suis serotype 2 porcine isolates. Strains were sequence type (ST) 28 (51%), ST25 (44%), and ST1 (5%). We identified nonrandom associations between STs and expression of the virulence markers suilysin (SLY), muramidase-relased protein (MRP), and extracellular factor (EF). Expression of pili encoded by the srtF and srtG pilus clusters was also nonrandomly associated with STs. ST1 strains were SLY+ EF+ MRP+ srtF pilus+ srtG pilus-. ST25 strains were SLY- EF- MRP- srtF pilus- srtG pilus+, and most ST28 strains were SLY- MRP+ EF- srtF pilus+ srtG pilus+. ST28 isolates proved essentially nonvirulent in a mouse infection model; ST25 strains showed moderate virulence and ST1 isolates were highly virulent. ST1 is responsible for a high proportion of S. suis disease in humans worldwide. Its presence in North America indicates that potential zoonotic S. suis outbreaks in this continent cannot be disregarded.